Mitigation of notch sensitivity by controlled alignment of carbon nanotubes in epoxy using electric field application. (October 2021) - Pothnis, Jayaram R.; Kalyanasundaram, Dinesh; Gururaja, Suhasini
Abstract: A novel process design methodology for mitigating notch sensitivity in CNT/epoxy nanocomposite plates containing rectangular filleted notches has been presented in this work. Multi-wall carbon nanotubes (MW-CNTs) were selectively oriented in target zones around the notch using a controlled transient non-uniform electric field to alleviate stress concentration effects during tensile loading. The improvement in overall tensile strength of the notched nanocomposite plates with three different orientations (0°, 45° and 90°) with respect to the loading direction is demonstrated. A maximum improvement in tensile strength of 55% in comparison to neat epoxy resin was observed in case of 45° notch orientation by employing this technique. Full-field strains obtained using digital image correlation (DIC) during testing provide a detailed look at the deformation progression around the notch. Fractography analysis was performed to identify the mechanisms in support of the observations made. This study has wide ranging applications to polymer matrix composite laminates with notches.